HUBUNGAN PENGHAYATAN NILAI ISLAM ANGGOTA TENTERA DARAT BERDASARKAN PROGRAM PENDIDIKAN ISLAM FARDU AIN DI LEMBAH KLANG - Mohamed Radzi Musa (Tesis, 2021)
The objective of this study is to examine the relationship between curriculur factors, coaches, infrastructure, and the role of motivation as a mediating variable on the appreciation of Islamic values among members of the Army.